Congress as a deviant organization: an application of Ermann and Lundman’s organizational deviance framework - Peoples, Clayton D. (Deviant behavior, 2020)
In 1978, Ermann and Lundman put forth the most sophisticated organizational deviance framework to date. They conceptualized organizational deviance as actions by an organization that interfere with the flow of benefits to actors with legitimate claims upon that organization. Further, they stipulated that these claims are protected by "controlling organizations." We apply Ermann and Lundman’s framework to Congress and conclude that it is a deviant organization. We then contemplate the challenges to social control that congressional deviance poses, and contend that the "exempt status" enjoyed by Congress - in that it writes its own rules and polices itself - should be removed.